EU Citizenship, Free Movement, and Covid-19 in Romania - Mantu, Sandra (Frontiers in Human Dynamics, 2020)
Traveling freely, smoothly and unburdened by excessive formalities and the adjoining right to reside in another EU state for work, leisure or study are the hallmarks of the mobility regime applicable to EU citizens and their family members. Measures taken by the majority of EU states to deal with Covid-19 have severely disrupted EU mobility and led to the reestablishment of internal border controls, the introduction of restrictions to travel and even travel bans. These obstacles to mobility have highlighted the EU economy’s reliance on EU migrant labor in several sectors, which was further exacerbated by the introduction of an EU travel ban at the external border. This contribution discusses measures taken by Romania that sought to restrict travel to and from Romania, while simultaneously allowing exceptions for nationals to travel to other EU states as essential workers. The Romanian response is discussed in relation to the wider EU attempts to reply to the proliferation of national measures affecting EU free movement and the functioning of the internal market and as an illustration of the need to ensure that mobility goes hand in hand with protection.